The Students’ Perception toward Warming-Up Activities in Increasing the Motivation in Learning Maritime English II - Yoana G.P. Lengari; Maria D.A. Pavita (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
This study aims to determine the students’ perception towards warming-up activities to boost their motivation in learning Maritime English II. The object of this study is 18 students from the fourth-semester Engineering Program in Akademi Maritim Nusantara Cilacap. This is a descriptive-qualitative study. The data for this study is obtained from observation and questionnaires. The questions consisted of three categories that indicated the students’ perception toward warming-up activities; they were (1) Indicators of Warming-up and Principles, (2) Indicators of Background Knowledge of Warming-up Activities, and (3) Indicators of Motivation and Warming-up Activities. The study showed that the students positively percieved warming-up activities in Maritime English II lessons. The questionnaire result showed that the majority of the respondents answered the questions with Strongly Agree and Agree for most of the questions given. It indicated that they positively perceived the warming-up activities as a way to help motivate them to learn Maritime English II.